VALIDITAS HADITS TENTANG PENGUTUSAN MUAZ KE YAMAN (Kajian Takhrij Hadis) - Taufiq, Muhammad (Alhurriyah, 2010)
A hadits about the mission of Muaz bin Jabbal to Yemen when he was being a judge is identically showing that he was an expert to decide a law by a way of ijtihad. Ijtihad is an effort to take a law by an individual interpretation and judgment. This caused a positive appreciation of Prophet Muhammad, we could see this when the Prophet Muhammad asked him about some problems of Moslems societies that might be faced by him in the next time after. This hadits is a very popular among the authors of books discuss about ushul fiqh and fiqh. Moreover, this hadits is being comprehended as a justification of Prophet Muhammad towards the allowance of the determining of Islamic law. From the perspective study of hadits, knowledge about takhrij is like a â€œknifeâ€ analyzing to know about the existence and quality of a hadits. By using the study, we could see whether a hadits could be accepted or not (maqbul or mardud). Based on the writerâ€™s study, the writer could find that the hadits was regarded as a weak hadist (dloif). This was caused that one of the Rawi (a person who told about the hadits) was unknown about his personality that commonly we called it as riwayat majhul. Moreover some ulamaâ€™ hide â€œMr. Xâ€ from the stripe for ending the hadits. As caused by the popularity of the hadits and the finding from another story (riwayat) to reveal the same case, then the hadits is able to be used as a proponent reason (dalil) towards the decision (nash) about the allowance and command for ijtihad.